2007
DOI: 10.1097/01.brs.0000258882.96011.47
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fracture Mechanism and Morphology on the Reliability and Validity of Two Novel Thoracolumbar Injury Classification Systems

Abstract: Although both schemes were noted to have substantial reproducibility and validity, our results indicate the TLISS is more reliable than the TLICS, suggesting that the mechanism of trauma may be a more valuable parameter than fracture morphology for the classification and treatment thoracolumbar injuries. Since these injury characteristics are interrelated and are critical to the maintenance of spinal stability, we think that both concepts should be considered during the assessment and management of these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 8 publications
2
58
1
6
Order By: Relevance
“…In general, the main concern of contemporary classification systems for TL injuries is that they are limited either by excessive complexity or the lack of inclusiveness [10,27]. Many original reports describing common TL injury classifications lack a rigorous scientific foundation [10].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the main concern of contemporary classification systems for TL injuries is that they are limited either by excessive complexity or the lack of inclusiveness [10,27]. Many original reports describing common TL injury classifications lack a rigorous scientific foundation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Injuries were classified using the AO classification as well as the TLICS for thoracolumbar injuries. 2,10,14,16,20,23,25,27,29 Total operative time, blood loss, and length of hospital stay were obtained via chart review from the surgeon's operative note, the operating room records, and the discharge summary. Results are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in a total number of 21 included articles of this review. Eight studies evaluated the agreement on PLC injury evaluation [15][16][17][18][19][20][21][22], another eight studies evaluated the accuracy of detecting PLC injuries [23][24][25][26][27][28][29][30] and one study evaluated both agreement and accuracy [31]. Four studies reported on different validity components of PLC injuries [32][33][34][35].…”
Section: Search and Screening Resultsmentioning
confidence: 99%
“…In these classification validation studies, the assessment of the PLC status was part of the validation process of the TLISS [18][19][20][21][22] and TLICS [16,22]. Taking a closer look at the original paper introducing the TLISS classification, it becomes clear that neither the PLC, nor an injury of this structure, has been defined in detail [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation